The use of dried spent yeast as a low-cost nitrogen supplement in ethanol fermentation from sweet sorghum juice under very high gravity conditions - Sridee, Worawut; Laopaiboon, Lakkana; Jaisil, Prasit; Laopaiboon, Pattana (Electronic Journal of Biotechnology, 2011)
Dried spent yeast (DSY) was used as a low-cost nitrogen supplement for ethanol fermentation from sweet sorghum juice under very high gravity (VHG) conditions by Saccharomyces cerevisiae NP 01. The fermentation was carried out at 30ºC in a 5-litre bioreactor. The results showed that DSY promoted ethanol production efficiencies. The ethanol concentration (P), productivity (Qp) and yield (Yp/s) of the sterile juice (total sugar of 280 g l-1) supplemented with 8 g l-1 of DSY were not different from those supplemented with yeast extract and/or peptone at the same amount. The initial yeast cell concentration of 5 x 107 cells ml-1 was found to be optimal for scale-up ethanol production. In addition, an increase in sugar concentration in inoculum preparation medium (from 10 to 100 g l-1) improved the ability of the inoculum to produce ethanol under the VHG conditions. When S. cerevisiae NP 01 grown in the juice containing 100 g l-1 of total sugar was used as the inoculum for ethanol fermentation, the P, Qp and Yp/s obtained were 108.98 ± 1.16 g l-1, 2.27 ± 0.06 g l-1 h-1 and 0.47 ± 0.01 g g-1, respectively. Similar results were also observed when the ethanol fermentation was scaled up to a 50-litre bioreactor under the same conditions. The cost of the sweet sorghum for ethanol production was US$ 0.63 per litre of ethanol. These results clearly indicate the high potential of using sweet sorghum juice supplemented with DSY under VHG fermentation for ethanol production in industrial applications.